KONSEP AYAT-AYAT AL-QUR’AN VIS A VIS AYAT-AYAT SETAN DALAM KAJIAN ‘ULUMUL QUR’AN - Abu Khaer; Fatkhul Mubin (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2022)
This study is aimed at exposing the conception of the verses of the Qur'an vis a vis the Verses of Satan. Salman Rushdie with his work The Satanic Verses (Satanic Verses) once shocked the Islamic world, by trying to counter the belief of Muslims in the sacredness of the verses of the Qur'an. Uniquely, Rushdie's view is actually contained in the treasures of Islam itself, namely the Qissat al-gharānīq (Story of the Crane). Although its validity is doubtful, narrations about Satan's verses have been included in various commentaries, including: Tafsr al-Thabari, Tafsr al-Kasyaf, Tafs Jar Jalalayn and others. They raised the devil's whispering verse (gharānīq) when interpreting verse 52 of surah al-Hajj